The Role of Tumor Microenvironment and Immune Response in Colorectal Cancer Development and Prognosis - Wozniakova, Maria; Skarda, Jozef; Raska, Milan (Pathology oncology research, 2022)
Colorectal cancer (CRC) is one of the most common cancers worldwide. The patient's prognosis largely depends on the tumor stage at diagnosis. The pathological TNM Classification of Malignant Tumors (pTNM) staging of surgically resected cancers represents the main prognostic factor and guidance for decision-making in CRC patients. However, this approach alone is insufficient as a prognostic predictor because clinical outcomes in patients at the same histological tumor stage can still differ. Recently, significant progress in the treatment of CRC has been made due to improvements in both chemotherapy and surgical management. Immunotherapy-based approaches are one of the most rapidly developing areas of tumor therapy. This review summarizes the current knowledge about the tumor microenvironment (TME), immune response and its interactions with CRC development, immunotherapy and prognosis.
Keywords: Tumor Microenvironment; imunita; Immunity; nádorové mikroprostředí; consensus molecular subtypes; Colorectal Neoplasms; immune cells; tumorigenesis; colorectal cancer; Humans; kolorektální nádory; lidé; imunoterapie; Immunotherapy; Prognosis; prognóza; immunoscore; tumor microenvironment